(untitled) (Bangladesh Journal of Medical Science, 2021)
Aim and Objective:The literature of Ilmul Amraz occupies a pedestal position in Unani medicine.The literature, however, is scattered among many manuscripts and requires being collected and compiled for better understanding and comprehension of disease concepts of Unani medicine. The material has been collected from the original resourcesof early Abbasid caliph (from7th-9thC.E) till the period of Al-Razi and briefly introduced in this article. Material and Methodology: The proposed literary research is conducted through ‘input-processing-output’ approach. The literature has been collected from different classical texts, reference books and various digitalized mode. Conclusion: The present review article underlines the contributions of Arab physicians, their original works, innovations, and practical experiences. The impact of theoretical contribution of Al Razi manifests in ancient Greco-Roman theory of diseases. Bangladesh Journal of Medical Science Vol.20(2) 2021 p.228-233